2018
DOI: 10.1002/oby.22348
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of Resveratrol on Blood Lipid Levels in Patients with Type 2 Diabetes: A Systematic Review and Meta‐Analysis

Abstract: Objective: Few studies have considered the effect of resveratrol on blood lipid levels, and the results of these studies are inconsistent. In this study, the first meta-analysis on the effect of resveratrol on blood lipid levels in patients with type 2 diabetes was conducted. Methods: This study used keywords such as type 2 diabetes, total cholesterol, triglyceride (TG), high-density lipoprotein, low-density lipoprotein, and resveratrol and their abbreviations, free words, and related words to search PubMed, C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
20
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 33 publications
4
20
1
Order By: Relevance
“…To address this unique clinical difficulty, frontline T2D drug metformin has been explored as an addition to insulin treatment in such T1D patients [39]. Preclinical data showed that resveratrol was efficacious in preventing metabolic syndrome related to high-fat feeding, including insulin resistance, which lead to the pursuance of randomized clinical trials in T2D patients [40,41]. Evidently, resveratrol is known to recover dysregulated glucose homeostasis, while decreasing insulin resistance in T2D patients as reported by a myriad of clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…To address this unique clinical difficulty, frontline T2D drug metformin has been explored as an addition to insulin treatment in such T1D patients [39]. Preclinical data showed that resveratrol was efficacious in preventing metabolic syndrome related to high-fat feeding, including insulin resistance, which lead to the pursuance of randomized clinical trials in T2D patients [40,41]. Evidently, resveratrol is known to recover dysregulated glucose homeostasis, while decreasing insulin resistance in T2D patients as reported by a myriad of clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…Also, previous studies reported that resveratrol mediates cholesterol clearance by raising hydroxycholesterol production through regulation of the expression of cytochrome P450 27‐hydroxylase enzyme (Bingham et al, ). HDL‐C formation was also stimulated by resveratrol through adjusting the expression of main cholesterol transporters (Zhao et al, ). In addition, studies reported that resveratrol contributes to preventing the conversion of LDL‐C to oxidized LDL (Liu, Chen, & Li, ).…”
Section: Discussionmentioning
confidence: 99%
“…While in our results, no differences were found in the HDL-c concentrations. The discrepancies between our results related to the lipid metabolism could be partly explained for the T2DM status attributable to the synergetic effects of anti-diabetic drug and resveratrol as well as lipid-lowering medication [ 28 ]. It is important to mention that incidence of T2DM in our population was lower compared to Zamora et al, reported [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…The lack of commercially available glucuronide and sulfate resveratrol standards is still an issue that hampers advancements in the quantification of total resveratrol metabolite. The lipophilic nature of resveratrol could facilitate the entry into the surface of albumin and lipoprotein, and these properties could confer benefits on lipid profile, avoiding the oxidation of LDL [ 28 , 37 , 38 ]. A study found that resveratrol metabolites, including trans -/ cis -resveratrol-3- O -glucuronide, and cis -resveratrol-3- O -glucoside, as well as free trans -resveratrol, were incorporated into the LDL of human participants after intake of moderate red wine, which could suggest the cardioprotective role of resveratrol on atherogenic markers and oxidative stress [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation